RUHE, Cornelia. 2020. La mémoire des conflits dans la fiction française contemporaine. Leiden/Boston: Brill/Rodopi (Francopolyphonies, 29). - Burtscher-Bechter, Beate (apropos [Perspektiven auf die Romania], 2020)
Rezension